For the equation \( x^2 + 4x + 3 = 0 \):
Completing the statements:
- The value of a is 1 (the coefficient of \( x^2 \)).
- The value of b is 4 (the coefficient of \( x \)).
- The value of c is 3 (the constant term).
Finding one solution to the equation:
To find the solutions of the equation, we can factor it or use the quadratic formula. The equation factors as follows:
\[ x^2 + 4x + 3 = (x + 1)(x + 3) = 0 \]
Setting each factor to zero gives us the solutions: \[ x + 1 = 0 \quad \Rightarrow \quad x = -1 \] \[ x + 3 = 0 \quad \Rightarrow \quad x = -3 \]
Thus, one solution to the equation is -3.
Answers for Question 3:
Among the provided response options, the correct response would be:
- (-3, 0)
Summary of your answers:
- Value of a: 1
- Value of b: 4
- Value of c: 3
- One solution of the equation: -3 (in the coordinate format, it's (-3, 0))